EXPERT SYSTEM FOR IDENTIFYING DENTAL DISEASES USING THE DEMPSTER-SHAFER METHOD BASED ON ANDROID - khatulistiwa, jamrud; arnita, arnita (Journal of Informatics and Data Science, 2024)
The ability of an expert system to identify symptoms is not as optimal as that of a specialist because there are still uncertainties that can cause errors in identification. Therefore, the Dempster-Shafer method is used to calculate expert system uncertainty. This dental disease identification system is designed as an Android application. Then, system accuracy is tested by comparing system identification results with test data from medical records of patients with dental disease. From the results of the tests that have been carried out, the match value is obtained for as many as 26 suitable cases. So as to produce a percentage of accuracy of 86.67% in 30 cases. Overall, it can be concluded that the use of the Dempster-Shafer method in this expert system is valid for identifying dental diseases.